Adicção a smartphone e características do sono de estudantes universitarios brasileiros durante a pandemia da COVID-19 - Juan Diego Torres Ribeiro (2021)
Brazil is one of the epicenters of the COVID-19 pandemic in the world. Thus, the maintenance of social isolation measures is necessary to contain the spread of the virus. A large part of the population performs professional and academic activities remotely and there has been a considerable reduction in leisure options. These factors may have contributed to the increased use of electronic media, including smartphones. The problems related to smartphone overuse have become increasingly important and scientific evidence indicates that individuals can develop smartphone addiction. This condition has similar aspects to other forms of physical or psychological addictions. The present study evaluated the association between smartphone addiction and sleep characteristics in Brazilian university students in social isolation due to the COVID-19 pandemic. A total of 547 students selected from the snowball sampling method participated in this cross-sectional study. Participants answered a questionnaire on the Google Forms platform about sociodemographic data, information about smartphone use and the Brazilian versions of the Smartphone Addiction Scale (SAS-SV) and the Pittsburgh Sleep Quality Index (PSQI-BR). Descriptive, bivariate and multifactorial logistic regression analysis were used (p˂0.05). The mean age of participants was 24.9 years (±5.5), and the majority were female (74.5%). The prevalence of smartphone addiction was 48.3% and sleep disorders was 22.5%. The PSQI-BR total score was higher among students with smartphone addiction (p˂0.001). The final logistic regression model evidenced that students who used smartphones to access social networks (OR = 3.681; 95% CI: 2.18 – 18.71), for entertainment (OR = 2.121; 95% CI: 1.41 – 3 .19) and those with a high score of the PSQI-BR domain of daytime dysfunction (OR = 1.487; 95% CI: 1.15 – 1.92) were more likely to belong to the group with smartphone addiction. Thus, it was concluded that using smartphones for entertainment and accessing social networks, as well as having difficulty concentrating on daytime activities, were positively associated with smartphone addiction among university students. Participants with high levels in the PSQI-BR daytime dysfunction domain were more likely to belong to the smartphone addiction group. The high prevalence of smartphone addiction found in this study points to the need for further discussion on this topic. Especially considering that the literature indicates positive associations between excessive smartphone use and biopsychosocial harms. It is important to alert health and education professionals, as well as to make the population aware of the risks and consequences of smartphone addiction. The development of public policies is essential, aiming to educate the population for the rational use of this technology and to prevent possible long term health impacts, which are still uncertain.